Trastuzumab deruxtecan for the late lines of treatment for HER2-low metastatic breast cancer: a clinical case - R. A. Murashko; S. V. Sharov; E. P. Chashnikova (Опухоли женской репродуктивной системы)
The new generation conjugate trastuzumab deruxtecan (Т-DXd) is indicated for the treatment of adult patients with unresectable or metastatic HER2-positive breast cancer (BC) who have previously received a drug regimen containing anti-HER2 targeted agents, as well as for the treatment of adult patients with unresectable or metastatic HER2-weakly positive breast cancer (1+ or 2+ by immunohistochemistry/negative by in situ hybridization) who have received prior systemic therapy for metastatic disease or who have relapsed during or within 6 months of completion of adjuvant chemotherapy. Given the positive data on the use of Т-DXd in different populations of patients with metastatic BC, it is advisable to collect data from real-world clinical practice to expand treatment options.A 67-year-old female patient received Т-DXd as a sixth-line therapy for recurrent HER2-low metastatic BC, with a 20 % reduction in the size of the liver metastasis and no progression during therapy. The data of the clinical case were collected as part of a study of Т-DXd monotherapy in patients with metastatic BC who had previously received at least 2 lines of systemic therapy, in the real-life practice of the Clinical Oncological Dispensary No. 1 of Krasnodar.The presented clinical case is consistent with the data of the clinical study DESTINY-Breast04 and shows the potential for using Т-DXd in real-life clinical practice in patients with metastatic HER2-weakly positive BC in late lines.